The ethnobotanical and socio-cultural aspects of common Myrtle (Myrtus communis L.) in the Beni Mellal-Khenifra region (Morocco) and socio-cultural aspects of common Myrtle (Myrtus communis L.) in the Beni Mellal-Khenifra region (Morocco) - Aabdousse, Jamal; Faida, Rahima; Boulli, Abdelali; Hassib, Aziz; Wahid, Nadya (Ethnobotany Research and Applications, 2020)
Background: The study of ethnobotany is to create a catalog of medicinal plants in order to preserve the indigenous knowledge and to promote the sustainable exploitation of these plant resources. The aim of this study was to evaluate the ethnobotanical of commercialized medicinal plants (MAPs) focusing on Myrtle species, in the Beni Mellal-Khenifra region of Morocco. Methods: A series of ethnobotanical and socio-cultural surveys were conducted among the local population of the study area. Results: The present study has allowed us to reveal that the most of commercialized MAPs are used primarily in the care of the digestive system and the glands attached to the digestive tract. The foliage is the most used part for treatment. Decoction is the most practiced method by the local population. Among the commercialized MAPs there is Myrtle specie that used mainly in hair care and in the treatment of digestive tract abnormalities. The female gender, aged between 40 and 50 years, traditionally uses the commercialized MAPs as well as the Myrtle more than the male gender. Whatever the gender, the illiterate use MAPs more than the educated. Conclusions: This study shows the wealth of knowledge of the local population which has a rudimentary social level. Considering the importance of Myrtle use in Morocco or internationally and following its cosmetic and therapeutic virtues, it is time to raise the awareness and enrich the traditional know-how of this species in the region of Beni Mellal-Khenifra within a framework of sustainable manner. Key words: Myrtus communis L., therapeutic uses, ethnobotany, Beni Mellal- Khenifra region.